Factors affecting sugarcane production in Pakistan - Adnan Nazir; Ghulam Ali Jariko; Mumtaz Ali Junejo (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
This study was undertaken to identify the factors affecting sugarcane production in Pakistan. Data were collected from 387 sugarcane growers from Sindh, Punjab and NWFP province. Data were collected during the period 2007-08. The study reveals that the costs of inputs of sugarcane i.e. urea, DAP, FYM, land preparation, seed and its application, weeding and cost of irrigation were the important factors which influenced on the returns of sugarcane growers. The effectiveness was examined by using the Cobb- Douglas production function; MVP and allocative efficiency were calculated. The coefficient of multiple determinations R2 was 0.9249, which indicated that 92% variation in the cost of inputs was explained by all explanatory variables and the adjusted R2 was 92%. The F-value was 666.94 and was highly significant at 5% level of significance, indicating that the regression model was well fitted. The high prices of inputs, low price of output, delay in payments and lack of scientific knowledge were the major problems in sugarcane production. In order to enhance the productivity of sugarcane in the country, government should solve the identified problems to increase the income of sugarcane growers.
Keywords: 330; Sugarcane; urea; weeding; cost of irrigation; land preparation; seed; Cobb-Douglas function; resource allocation efficiency